Conifers Network: Report of the first meeting,22-24 March 2000, Brdo/Kranj, Slovenia - Turok, J.; Mátyás, Cs.; Fady, B.; Borelli, S.; European Forest Genetic Resources Programme; International Plant Genetic Resources Institute (2001)
Highlights on progress made in gene conservation of Norway spruce (Picea abies) in Europe. Outputs of the EUFORGEN Picea abies Network.Assessing priorities for the EUFORGEN Conifers Network. Workplan. Four main areas of involvement (information, policy and legal issues, technical guidelines and public awareness) were discussed in three working groups. Each working group proposed a set of activities. They provide the basis for this workplan, agreed during the final session of the meeting.